Somatic USP8 mutations are frequent events in corticotroph tumor progression causing Nelson's tumor. Issue 1 (January 2018) - Pérez-Rivas, Luis G; Theodoropoulou, Marily; Puar, Troy H; Fazel, Julia; Stieg, Mareike R; Ferraù, Francesco; Assié, Guillaume; Gadelha, Monica R; Deutschbein, Timo; Fragoso, Maria C; Kusters, Benno; Saeger, Wolfgang; et al.
Abstract : Objective: Somatic mutations in the ubiquitin-specific protease 8 ( USP8 ) gene are frequent in corticotroph tumors causing Cushing's disease (CD). Corticotroph tumor progression, the so-called Nelson's syndrome (NS), is a potentially life-threatening complication of bilateral adrenalectomy in patients with refractory CD that is caused by the development of an ACTH-secreting tumor of the pituitary gland. Whether USP8 alterations are also present in progressive Nelson's tumors has not been studied in detail so far. Design and Methods: Retrospective, multicenter study involving tumors from 33 patients with progressive corticotroph tumors (29 females) and screening for somatic mutations on the mutational hotspot of the USP8 gene in the exon 14 with Sanger sequencing. Results: Fifteen out of 33 tumors (45%) presented with a mutation in the exon 14 of USP8, with c.2159C>A (p.Pro720Gln) being the most frequent (9/33), followed by c.2155_2157delTCC (p.Ser718del, 4/33) and c.2152T>C (p.Ser718Pro, 2/33). This prevalence is similar to that previously reported for CD. Mutations were found exclusively in females. Other variables, such as age at diagnosis with NS, body mass index, hyperpigmentation, visual field defects, adenoma size or mortality, did not significantly differ between patients with wild-type and mutant tumors. Patients with USP8 mutant tumors exhibited higher levels of plasma ACTH after surgery (median: 640 vs 112 pg/mL, P = 0.03). No differences were observed in ACTH normalization (<50 pg/mL) and tumor control after surgery for Nelson's tumor. Conclusion: Somatic mutations in USP8 are common in Nelson's tumors, indicating that they do not drive the corticotroph tumor progression that leads to NS, and may be associated with a less favorable biochemical outcome after surgery for Nelson's tumor.